Analisis Pengobatan Tradisional dari Bahan-bahan Alam pada Masyarakat Aceh Jaya sebagai Bentuk Kearifan Lokal - Ervilita, Ria; Mardhiah, Ainun; Shaleh, Muhamad; Wagustina, Silvia; Makmur, T.; Djafar, Tasliati (UNIVERSITAS SERAMBI MEKKAH, 2023)
The people of Aceh Jaya are people who are still hold firm with local culture from generation to generation, one of which is in traditional medicine using natural ingredients. Local wisdom has a close relationship with the culture or tradition of an area.Various local wisdom practices that are still maintained by the Indonesian people can be one of the strategies for environmental protection and management. The purpose of this study is to analyze the local wisdom of the people of Aceh Jaya which is still preserved, especially in traditional medicine using natural ingredients. This type of research is descriptive qualitative through data collection techniques of observation, interviews and documentation. The data were analyzed using the Miles and Huberman model. The results of the study were obtained that Balakacida leaves are used by the people of Aceh Jaya to treat wounds, hibiscus leaves can treat fever, jujube leaves to treat smallpox, a mixture of sunti, onion and salt is used to treat possessed, water henna leaves to treat ulcers, coconut fruit flowers can treat smallpox,Jatropha curcas leaves gum for diarrhea and flatulence medicine, peacock flower leaves can treat fever,kapuk leaf (Ceiba Petandra) can treat cough, kedondong forest (spondias pinnata) to treat coughs, and Sembung leaves (blumea balsamifera) can treat fever. The conclusion of this study is that the people of Aceh Jaya still use traditional medicine from natural ingredients as a form of local wisdom that is still maintained.